2005
DOI: 10.1152/ajprenal.00058.2004
|View full text |Cite
|
Sign up to set email alerts
|

Expression of epidermal growth factor in the developing rat kidney

Abstract: Epidermal growth factor (EGF) is important in mammalian renal development. In our study, we investigated the detailed distribution and the time of the first appearance of EGF in developing rat kidney. Kidneys from embryonic 18 (E18)- and 20-day-old (E20) fetuses, postnatal 1 (P1)-, 3 (P3)-, 7 (P7)-, 14 (P14)-, and 21-day-old (P21) pups, and adults were processed for immunohistochemistry and electronmicroscopy. In adult rat kidney, EGF immunoreactivity was found in distal tubule including the thick ascending li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 35 publications
0
13
1
Order By: Relevance
“…Although Toubeau et al (1994) and Jung et al (2005) have observed the immunolocalizations of EGF in distal convoluted tubules and the thick ascending limb of Henle's loop of adult rat kidneys, our results revealed that EGF-positive cells localized to the proximal and the distal tubules in the kidney of immature rats indicating the difference of immunolocalization of EGF in the kidney between adult and immature animals . There are controversial reports on the involvement of EGF on the proliferative activity of the adult kidney.…”
Section: Effects Of Uninephrectomy On the Cell Proliferation And Egf contrasting
confidence: 91%
“…Although Toubeau et al (1994) and Jung et al (2005) have observed the immunolocalizations of EGF in distal convoluted tubules and the thick ascending limb of Henle's loop of adult rat kidneys, our results revealed that EGF-positive cells localized to the proximal and the distal tubules in the kidney of immature rats indicating the difference of immunolocalization of EGF in the kidney between adult and immature animals . There are controversial reports on the involvement of EGF on the proliferative activity of the adult kidney.…”
Section: Effects Of Uninephrectomy On the Cell Proliferation And Egf contrasting
confidence: 91%
“…The relative frequency of the morphologic and functional subtypes in the cortical and medullary TAL suggests that HBC cells correspond to S cells and LBC cells to R cells (3). Molecular characterization of this heterogeneity is still rudimentary; however, R and S cells clearly differ in the expression pattern of EGF (6) and NKCC2 (4). The functional correlates of this heterogeneity are discussed in the following sections.…”
Section: Anatomy and Morphologymentioning
confidence: 99%
“…Most of the ErbB-family ligands are expressed in the kidney (see Table 2 for some examples), and their expression could be dramatically changed during renal development or in pathological conditions (49,71,130). EGF and its related growth factors are present in the lumen at levels much higher than in plasma.…”
Section: Erbb Ligandsmentioning
confidence: 99%